2022
DOI: 10.1016/j.cgh.2020.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Time Pattern of Recurrences After Local Endoscopic Resection of T1 Colorectal Cancer: A Meta-analysis

Abstract: High-risk: 7.0% Low-risk: 0.7% BACKGROUND & AIMS:Growing numbers of patients with T1 CRC are being treated with local endoscopic resection only and as a result, the need for optimization of surveillance strategies for these patients also increases. We aimed to estimate the cumulative incidence and time pattern of CRC recurrences for endoscopically treated patients with T1 CRC. METHODS:Using a systematic literature search in PubMed, EMBASE, Web of Science and Cochrane Library (from inception till 15 May 2020), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 92 publications
4
53
1
Order By: Relevance
“…There is a consensus from most studies that rectal T1 cancer presents a higher recurrence rate than colon T1 cancer, regardless of the treatment strategy [43][44][45][46][47]. In a single-center study of 930 T1 CRC patients, Kouyama et al reported that rectal location was a significant risk factor for recurrence in the total population, including endoscopic resection alone and surgical resection.…”
Section: Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…There is a consensus from most studies that rectal T1 cancer presents a higher recurrence rate than colon T1 cancer, regardless of the treatment strategy [43][44][45][46][47]. In a single-center study of 930 T1 CRC patients, Kouyama et al reported that rectal location was a significant risk factor for recurrence in the total population, including endoscopic resection alone and surgical resection.…”
Section: Recurrencementioning
confidence: 99%
“…Yoda et al and Yoshii et al reported a similar tendency (rectum, 9.9% (10/101) and 14.5% (8/55); colon, 1.5% (5/ 327) and 2.3% (9/323), respectively) [44,45]. In 2020, a meta-analysis of 11 studies by Dang et al revealed that the rectal cancer also indicated a higher recurrence rate than the colon cancer (colon, 0.8%, 95%CI 0.2-2.8; rectum, 5.7%, 95% CI 2.0-15.2) [47]. Finally, Ikematsu et al investigated the recurrence rate between the colon and rectum dividing 758 T1 CRC patients into two groups according to the LNM risk in a multicenter study [46].…”
Section: Recurrencementioning
confidence: 99%
“…There exists no literature on the benefit of sequential imaging over time. Two recent meta-analyses showed that the cumulative incidence of distal cancer recurrence was 3.5% and 5.5% after the endoscopic resection of high-risk T1 carcinomas [22,23]. The present study demonstrates the poor performance of monitoring, with only one case of metastasis detected and four missed diagnoses among the 121 patients with T1 cancers followed up by imaging.…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 59%
“…Nevertheless, some authors continue to believe that patients with high-risk T1 CRC should be offered personalized surveillance through shared decision-making while also taking into account the physical status and life expectancy of the patient [23]. For this reason, the issue of imaging surveillance should be discussed in multidisciplinary tumor meetings, which was not the case in this study, where only one third of the patient charts were presented to discuss only therapeutic management.…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 93%
“…Paul Didden, MD, PhD 1 Rixta A.H. van Eijck van Heslinga, BSc 1 , Matthijs P. Schwartz, MD, PhD 2 , L.R. Arensman, MD 3 , Frank P. Vleggaar, MD, PhD 1 , Wilmar de Graaf, MD, PhD 4 , Arjun D. Koch, MD, PhD 4 , Michael. Doukas, MD, PhD 5 , Miangela M. Lacle, MD, PhD 6 , Leon M.G.…”
Section: Relevance Of Polyp Size For Primary Endoscopic Full-thicknes...mentioning
confidence: 99%